Corrigendum to 'Detailed FE and DE Modelling of Stone Masonry Arch Bridges for the Assessment of Load-carrying Capacity': Procedia Engineering 114 (2015) 854–861. (2015) - Costa, C.; Arêde, A.; Morais, M.; Costa, A.
Abstract : The authors regret the mistake in the name and affiliation of the fourth author in the original manuscript and typos in Tables 1, 5 and 7. The corrected list of authors and affiliations for this paper is as shown above. In Table 1, fifth column, instead of '30.2' should be '30.2E-3' and in sixth column instead of '3.25 - 23.73' should be '3.25E-3 - 23.73E-3'. In Table 5, sixth column, instead of 'ϕ(°)' should be 'tanϕ'. In Table 7, last line, instead of '4.5 P' should be '4.6 P'. The authors would like to apologise for any inconvenience caused.